Peran Keimigrasian dalam Menangani Kasus Penyalahgunaan Izin Tinggal oleh Warga Negara Asing - Annisaa Luthfi Amalia; Sugito (Fakultas Hukum, Universitas Warmadewa, 2023)
Cases of abuse of residence permits committed by foreign nationals are motivated by very easy access to come and go from Indonesian territory. Cases of abuse of residence permits can have a negative impact on the emergence of security threats such as drug smuggling, terrorism and human trafficking. The Immigration as the gatekeeper for the entry and exit of foreign nationals has a strategic role in preventing and taking action against the practice of abusing residence permits. This research will explain about the role of Immigration, especially the Special Class I Border Control Immigration Office Surabaya in handling abuse of residence permits in the Surabaya area. This case study research uses a qualitative approach with primary data sources from interviews and studies of state documents as well as secondary data from articles and journal. The findings obtained indicate the role of Immigration, especially the Special Class I Border Control Immigration Office Surabaya in terms of prevention through supervision and the establishment of a Foreigner Monitoring Team. Meanwhile, prosecution of violators is carried out through administrative, criminal, detention, and projustia measures.